Contributions of polarized dislocation walls, internal stresses and vacancies on hydrogen trapping processes in tensile strengthening (100) nickel single crystal. (15th February 2023) - Oudriss, A.; Martin, F.; Creus, J.; Bouhattate, J.; Marchetti, L.; Feaugas, X.
Abstract: Multiscale impact of dislocation patterns on hydrogen diffusion and trapping mechanisms has been investigated in multi-slip tensile strengthening nickel single crystal. A thorough analysis of dislocation densities and distribution, resulting long-range internal stresses and vacancies concentration was performed at different levels of plastic deformation to precisely characterize the different trapping sites and their impact on apparent diffusion coefficient. Both factors, which govern the hydrogen distributions, have been exanimated using an original analyze combining electrochemical permeation and thermal desorption mass spectroscopy. The results revealed a slowing of the hydrogen diffusion resulting from the phenomenon of trapping by dislocations at different scales. An energetic approach made it possible to associate the reversible trapping with the elastic field of dislocations, and the irreversible trapping with the core of dislocations and vacancies. Moreover, the analyses highlight an implication of the long-range internal stress in the increase of the apparent hydrogen solubility in relation with dislocation cells formation. Finally, a contribution of vacancies to hydrogen trapping is demonstrated with a competition between the formation of vacancies induced by plastic strain and hydrogen ingress. Graphical abstract: Image, graphical abstract